Efficient collection of perrhenate anions from water using poly(pyridinium salts) via pyrylium mediated transformation. Issue 2 (17th December 2021) - Li, Xiaorui; Chai, Liyuan; Ren, Junyu; Jin, Linfeng; Wang, Haiying; Li, Yiming; Ma, Shengqian
Abstract : Poly(pyridinium salts) composed of cationic pyridinium groups with benzene-rich motifs demonstrated high efficiency and selectivity in the capture of ReO4 − from SO4 2− containing water. Abstract : Poly(pyridinium salts) (PPSs) with positive charges on the backbones were designed and synthesized from the transformation of bispyrylium salts. Such materials exhibited good uptake capacity for rhenium capture from water, and excellent selectivity of ReO4 − from competing anions. Furthermore, the advantages of facile synthesis and large-scale preparation make this material promising for practical use in industry.